2022
DOI: 10.1111/apa.16266
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the use of standard SIDS definitions in the English language literature over a three‐year period (2019–2021)

Abstract: Aim To evaluate the use of the three standard definitions of sudden infant death syndrome (SIDS) in the contemporary literature. Methods A search was undertaken of the US National Library of Medicine ‘PubMed’ database for all research articles listed under ‘sudden infant death syndrome’ or ‘SIDS’, from 2019 to 2021 accessible through the University of Adelaide library. Results 564 papers had keywords ‘sudden infant death syndrome’ or ‘SIDS’. 300 papers were not included in the study as they were not written in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Unfortunately, to date, SIDS results in a significant proportion of deaths during infancy worldwide despite the improvement in healthcare and medical research. The etiology of SIDS is unknown, but it is considered a multifactorial disorder (DiMaio and Molina, 2022;Tan and Byard, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, to date, SIDS results in a significant proportion of deaths during infancy worldwide despite the improvement in healthcare and medical research. The etiology of SIDS is unknown, but it is considered a multifactorial disorder (DiMaio and Molina, 2022;Tan and Byard, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the increasing trend of not following standard definitions may hinder data interpretation and have a negative impact on the validity of SIDS research. In another paper in this issue, Tan et al analysed the use of standard SIDS definitions from 2019 to 2021 8 …”
Section: A Decline In Academic Rigour In Research On Sudden Infant De...mentioning
confidence: 99%
“…In case these data were influenced by inadvertent selection bias, a more thorough study was then performed in which consecutive published papers over a 3‐year period (2019–2021) were examined. Of the 264 papers evaluated, 172 (65%) had no definition or idiosyncratic or incorrectly quoted definitions or incorrect referencing, with only 92 (35%) having one of the three standard definitions either quoted in full in the text or correctly referenced 20 . Thus, nearly two‐thirds of peer‐reviewed SIDS publications between 2019 and 2021 have not quoted or referenced internationally accepted definitions.…”
mentioning
confidence: 99%
“…Of the 264 papers evaluated, 172 (65%) had no definition or idiosyncratic or incorrectly quoted definitions or incorrect referencing, with only 92 (35%) having one of the three standard definitions either quoted in full in the text or correctly referenced. 20 Thus, nearly twothirds of peer-reviewed SIDS publications between 2019 and 2021 have not quoted or referenced internationally accepted definitions. This is a marked decrease of 33% from the 68% of papers that correctly used SIDS definitions in 2011.…”
mentioning
confidence: 99%